Data from UK genitourinary medicine clinics, 2006: a mixed picture. Issue 6 (1st October 2007) - Hughes, Gwenda; Simms, Ian; Leong, Geraldine
Abstract : Objective: To give an overview of the latest latest trends in diagnoses made and services provided by genitourinary medicine (GUM) clinics in the UK. Methods: Aggregate data collected from the KC60 statistical returns for GUM clinics in England, Wales and Northern Ireland and disaggregate data collected using the STI Surveillance System for GUM Clinics in Scotland. These data were collated and numbers of diagnoses were adjusted for missing clinic data. Results & Conclusion: Overall, numbers of new diagnoses of sexually transmitted infections (STIs) continued to rise in 2006. However, there was some evidence of improvement, with new diagnoses of gonorrhoea falling for the fourth successive year. Chlamydia continued to be the most common STI diagnosed in GUM clinics, and the sharp rise in new diagnoses over the last 10 years was most likely associated with an increase in testing volume and accuracy. The highest rates of STI diagnoses continued, in the main, to be among 16–24-year-olds, and there were some notable rises among this age group also: new diagnoses of genital herpes in teenage women rose by 16% in 2006. Improving the sexual health of men who have sex with men (MSM) must remain a priority, as the increase in numbers of new STI diagnoses among MSM over the past 10 years continued unabated into 2006. However, despite facing the challenge of reducing patient waiting times, there has been a considerable rise in sexual health screens and HIV tests being provided by GUM services, and this could, if sustained, result in significant improvements in sexual health in the coming years.